New species of aquatic oligochaetes (Annelida: Clitellata) from groundwaters in karstic areas of northern Spain, with taxonomic remarks on Lophochaeta ignota Štolc, 1886 - Rodriguez, Pilar; Achurra, Ainara (Zootaxa, 2010)
We describe two new species: Gianius navarroi n. sp. (Phallodrilinae) and Isochaetides gianii n. sp. (Tubificinae), which were discovered during investigations on the groundwater oligochaete fauna in northern Spain. The present study contributes to the knowledge of the stygobiont oligochaete species in the Iberian Peninsula, which includes 21 species so far. Mature specimens of Lophochaeta ignota Štolc, 1886 were also collected at some sites, and are used to supplement the limited description of the reproductive organs known for the species to date. Taxonomy of the genus Lophochaeta Štolc, 1886 is discussed.